2018
DOI: 10.1111/nph.15175
|View full text |Cite
|
Sign up to set email alerts
|

GhWIP2, a WIP zinc finger protein, suppresses cell expansion in Gerbera hybrida by mediating crosstalk between gibberellin, abscisic acid, and auxin

Abstract: Cell expansion is a key determinant for the final size and shape of plant organ, and is regulated by various phytohormones. Zinc finger proteins (ZFPs) consist of a superfamily involved in multiple aspects of organ morphogenesis. However, little is known about WIP-type ZFP function in phytohormone-mediated organ growth. Using reverse genetics, RNA-seq and phytohormone quantification, we elucidated the role of a new WIP-type ZFP from Gerbera hybrida, GhWIP2, in controlling organ growth via regulation of cell ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 73 publications
(113 reference statements)
1
35
0
1
Order By: Relevance
“…Protoplasts were isolated from gerbera leaves as described previously (Ren et al, 2018). YFP-GhEIL1 [GhEIL1 fused to yellow fluorescence protein (YFP) driven by the CaMV35S promoter] and YFP empty vector (YFP driven by the CaMV35S promoter) were transfected into protoplasts.…”
Section: Subcellular Localizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Protoplasts were isolated from gerbera leaves as described previously (Ren et al, 2018). YFP-GhEIL1 [GhEIL1 fused to yellow fluorescence protein (YFP) driven by the CaMV35S promoter] and YFP empty vector (YFP driven by the CaMV35S promoter) were transfected into protoplasts.…”
Section: Subcellular Localizationmentioning
confidence: 99%
“…The empty pBS vector (EV) was co-transformed with different reporters as no-interaction controls. Finally, following the above transformations, protoplast samples were incubated at 24-26°C overnight, then harvested and analyzed using the dual-luciferase reporter assay system with a VeritasTM Microplate Luminometer (Promega, Madison, WI, USA) (Yoo et al, 2007;Ren et al, 2018).…”
Section: Dual-luciferase Reporter Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Massive studies showed that GA is not only involved in regulating the process of plant growth and development alone, but also in coordination with other plant hormones to function. For example, the crosstalk between GA, ABA and auxin can regulate cell expansion during organ growth in Gerbera hybrida [16]. By mediating ABA and GA biosynthesis exogenous auxin represses seed germination in soybean [17].…”
Section: Introductionmentioning
confidence: 99%
“…Plant growth is also controlled by the regulation of different hormone signals, including auxin, brassinolide, and abscisic acid (Ren et al, 2018). During the petal elongation growth process, auxin promotes cell elongation and increases the number of cells in the petal basal region, regulating flower growth and development (Wang et al, 2017).…”
mentioning
confidence: 99%